2016
DOI: 10.1084/jem.20160287
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic cell sphingosine-1-phosphate lyase regulates thymic egress

Abstract: Saba and collaborators show that dendritic cells generate the thymic sphingosine-1-phosphate gradient and regulate T cell egress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(67 citation statements)
references
References 50 publications
2
65
0
Order By: Relevance
“…More recently, conditional SPL KO mice have been developed that can be utilized to study the cell-type specific function of SPL in vivo (66). Investigating the function of SPL in the mice model will allow us to determine the importance of SPL during IAV infection in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, conditional SPL KO mice have been developed that can be utilized to study the cell-type specific function of SPL in vivo (66). Investigating the function of SPL in the mice model will allow us to determine the importance of SPL during IAV infection in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…S1P is rapidly metabolized by S1P phosphatase (SGPP) 22 to sphingosine or by S1P lyase 1 (SPL; also known as SGPL1) 23 to yield ethanolamine-1-phosphate and hexadecanol (C16 fatty aldehyde) (FIG. 1).…”
Section: Sphingolipid Metabolism and Cancermentioning
confidence: 99%
“…However a recent study by Zamora-Pineda et al 74 found that deletion of Sgpl in either TECs or thymic endothelial cells was not sufficient to cause a T-cell egress defect. In fact it was only the deletion of Sgpl in bone marrow-derived cells that resulted in reduced thymocyte egress and a concomitant intrathymic accumulation of mature SP thymocytes.…”
Section: Regulation Of S1p Levelsmentioning
confidence: 94%
“…TECs and endothelial cells have also been shown to express S1P lyase (Sgpl), an enzyme that degrades S1P to maintain low levels of S1P to regulate T‐cell egress. However a recent study by Zamora‐Pineda et al . found that deletion of Sgpl in either TECs or thymic endothelial cells was not sufficient to cause a T‐cell egress defect.…”
Section: The S1p–s1pr1 Axismentioning
confidence: 97%
See 1 more Smart Citation